2006
DOI: 10.1007/s10856-006-0596-6
|View full text |Cite
|
Sign up to set email alerts
|

Stability and release of antiviral drugs from ethylene vinyl acetate (EVA) copolymer

Abstract: The use of polymer based drug delivery systems in dentistry is a relatively new area of research with the exception of the inhibition of secondary caries by the release of fluoride ions from polyalkenoate cements and their predecessors silicate cements. The present study was to test on orally biocompatible material, ethylene vinyl acetate copolymer (EVA), for release of antiviral drugs at oral therapeutic levels over extended periods of time. We also determined their stability during film casting and release. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Specifically, we prepared the drug-loaded polymer EVAc, which has been previously shown to serve as a vehicle for long-term drug release in vivo. 34,35 We hypothesized that the polymer itself would induce FBGC formation and allow us to examine the effect of Rac1 inhibition on this process as well as the overall foreign body response. We found that localized release of NSC23766 in vivo resulted in a significant reduction of FBGCs, confirming the importance of Rac1 activation in the formation of FBGCs.…”
Section: Inhibition Of Fbgc Formation In Vivo By Prolonged Release Ofmentioning
confidence: 99%
“…Specifically, we prepared the drug-loaded polymer EVAc, which has been previously shown to serve as a vehicle for long-term drug release in vivo. 34,35 We hypothesized that the polymer itself would induce FBGC formation and allow us to examine the effect of Rac1 inhibition on this process as well as the overall foreign body response. We found that localized release of NSC23766 in vivo resulted in a significant reduction of FBGCs, confirming the importance of Rac1 activation in the formation of FBGCs.…”
Section: Inhibition Of Fbgc Formation In Vivo By Prolonged Release Ofmentioning
confidence: 99%
“…Drug loaded EVA polymer films were prepared by solvent evaporation technique according to our earlier studies [11][12][13][14][15]. Nystatin loaded samples with surfactants Tween and Cremophor were prepared similarly in drug to surfactant ratios of (1:1), (1:2) and (1:3).…”
Section: Preparation Of Thin Polymer Filmsmentioning
confidence: 99%
“…Our second objective is to study the influence of drug loading on the rate of release of nystatin, chlorhexidine diacetate and acyclovir from EVA. Our previous studies have shown the ability of EVA, a biocompatible copolymer to deliver drugs at constant concentrations for an extended period of time [11][12][13][14][15]. This copolymer system is able to release the drug over several weeks and therefore may be useful as a drug carrier in the treatment of oral infections.…”
Section: Introductionmentioning
confidence: 99%
“…The only previous report showed that this copolymer has been fabricated into electrospun nanofibers [ 35 ]. Recently, EVA has been intensively used for drug delivery and controlled drug release [ 36 , 37 , 38 , 39 ]. To date, there has been no report about the fabrication of groove-ridge topography in combination with the EVA copolymer as scaffold material and its application in RGC culture.…”
Section: Discussionmentioning
confidence: 99%